Determinação de vanádio em águas usando a técnica de difusão em filmes finos por gradientes de concentração - Luko, Karen Silva [UNESP] (2015)
The Diffusion Gradients in Thin Films technique (DGT) allows the in situ quantitative evaluation of the concentration of labile metals by deploying the device in an aquatic system. DGT can be used for different metals, but some adjustments are required, especially in relation to the binding layer to be used. In this study, Amberlite IRA 410 resin was evaluated as the binding layer for vanadium sampling by DGT in natural waters, which was then determined by inductively coupled plasma mass spectrometry. 1.5% agarose (0.08 cm) was used as the diffusive layer. By using the developed device, deployments were carried out at varying times (4 to 72 h). The experiment was conducted using a V-stock solution (V) and keeping some conditions stable as T=23.5 ± 0.5 ° C, ionic strength 0.03 mol L-1 and pH=5.5. It was also evaluated the effect of ionic strength (0.0003 to 1 mol L-1) and pH (3, 5, 7 and 9) on the retention of the analyte. Tests (solid phase extraction) aiming to evaluate discs exchange capacity showed a value of 40.8 μg V-1 g resin. An elution factor of 0.86 ± 0.05 was obtained. Immersion curve was characterized by excellent linear correlation (R2 = 0.9964) and a significant retention of V by the binding layer (slope> 0.0016 ng s-1). Diffusion coefficient of 7.13 ± 0.3 10-6 cm2 s-1 was obtained in agreement with the expected value (6.66 10-6 cm2 s- 1) suggesting that the developed binding agent is effective. The V uptake was not significantly affected for solutions with ionic strength up to 0.3 mol L-1, and it was efficient for the entire studied pH range. Furthermore, the technique provided a Cl- interference reduction in the V determination by ICP-MS, comparing the values obtained from this technique and the values obtained by direct measurement of the concentration of the solution. Tests carried out to identify other possible interfering ions showed no significant interfering influences on the retention of the analyte. Tests on...